Interaction between NFATc2 and the transcription factor Sp1 in pancreatic carcinoma cells PaTu 8988t - Malsy, Manuela (BMC Mol Biol, 2017)
BACKGROUND: Nuclear factors of activated T-cells (NFATs) have been mainly characterized in the context of immune response regulation because, as transcription factors, they have the ability to induce gene transcription. NFAT proteins are found in several types of tumors, for instance, pancreatic carcinoma. The role of NFATs in carcinogenesis is regulating central genes in cell differentiation and cell growth. NFAT proteins are primarily located in cytoplasm and only transported to the cell nucleus after activation. Here, they interact with other transcription factors cooperating with NFAT proteins, thus influencing the selection and regulation of NFAT-controlled genes. To identify and characterize possible interaction partners of the transcription factor NFATc2 in pancreatic carcinoma cells PaTu 8988t. METHODS: NFATc2 expression and the mode of action of Ionomycin in the pancreatic tumor cell lines PaTu 8988t were shown with Western blotting and immunofluorescence tests. Potential partner proteins were verified by means of immunoprecipitation and binding partners, their physical interactions with DNA pull-down assays, siRNA technologies, and GST pull-down assays. Functional evidence was complemented by reporter–promoter analyses. RESULTS: NFATc2 and Sp1 are co-localized in cell nuclei and physically interact at the NFAT target sequence termed NFAT-responsive promotor construct. Sp1 increases the functional activity of its binding partner NFATc2. This interaction is facilitated by Ionomycin in the early stimulation phase (up to 60 min). CONCLUSIONS: Oncological therapy concepts are becoming more and more specific, aiming at the efficient modulation of specific signal and transcription pathways. The oncogenic transcription partner Sp1 is important for the transcriptional and functional activity of NFATc2 in pancreatic carcinoma. The binding partners interact in cells. Further studies are necessary to identify the underlying mechanisms and establish future therapeutic options for treating this aggressive type of tumor.